The 28. Implementation of Contemporary Art Development in the Charm of Rampak Sekar Dance in Ganyen Village, Malasari Village - Fitriyah; Syaavila, Firly; Ismiyati; Hanif, Yastrin (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Art is a cultural element that possesses distinct characteristics that reflect the unique regional qualities differentiating one area from another. Traditional dance artistry is currently facing a decline in interest and abandonment by some members of the community, including children. If there is no interest in traditional dance art, it may face extinction as modern dance forms capture the attention of the younger generation for study. One of these traditional dances is the Rampak Sekar Dance. The Rampak Sekar Dance is performed in the Ganyen Village of Malasari District. This dance has managed to survive in the modern era because it blends traditional and contemporary elements to remain relevant. The Rampak Sekar Dance, managed by the women of Ganyen Village, often participates in competitions and events in the area. However, this art form has not seen significant growth due to challenges in understanding how to leverage available media and limited popularity. As a result, the community is seeking assistance to revitalize and continue the Rampak Sekar Dance, which was temporarily halted during the COVID-19 pandemic. Building on this situation, our group has decided to serve in the field of art, targeting both children and adults. This decision was prompted by our self-analysis during our Community Service Program (KKN) in the RW 08 area of Ganyen Village, Malasari District. After conducting social observations, analysis, and interviews with local residents, we aim to strengthen our understanding of this dance and its cultural significance.